Argumentation As Critically Oriented Pedagogical Dialogue - Rapanta, Chrysi (Informal Logic, 2019)
Argumentation in educational contexts has been proposed as a dialogic practice that stimulates and promotes students’ critical thinking. However, the way critical thinking relates to argumentation is still not clear in the literature. This essay proposes the exploration of the concept of criticality, as manifested in students’ and teachers’ contributions within argumentative interactions, as the basis for the redefinition of “pedagogical dialogue” as a dialogue oriented towards critical argumentation. The main characteristics of this type of dialogue are described, shedding light on the connection between argumentation and critical thinking. These characteristics are illustrated through examples drawn from classroom interactions.